Analisis Kemampuan Pengelolaan Asset Terhadap Kinerja Usaha Pada Pelaku UMKM di Kota Batam Ketika Pandemi COVID-19 - Hardi Bahar; Emi Lestari (Journal of Applied Business Administration, 2022)
Small and Medium Enterprises (MSMEs) around the world are receiving a considerable impact due to Covid-19. The impact of covid-19 on MSMEs certainly has a problem that inhibits the business in the form of the community still lacking in improving the performance of its business. In this case if the ability to manage assets in running a business then can encourage the success of his business to cover the weaknesses he faces. Of course, this research has the aim to find out how asset management capabilities affect the performance of MSMEs in MSMEs in Batam city which has a population and a sample of 122 respondents. The data processing used using Smart PlS 3 Software Application by testing descriptive statistic analysis and inference statistic in the form of Inner and Outer Model using first and second order in the research model. The results of the research include asset management capabilities in weak or low performance while asset management capabilities have a significant effect on MSME Performance.